Primary malignant teratoma of the mediastinum with poor outcome: A case report - Sazdanić-Velikić Danica; Škrbić Dušan; Považan Đorđe; Đurić Mirna; Vučković Dejan; Sečen Nevena (Vojnosanitetski Pregled)
Introduction. About 5%–10% of mediastinal tumors in adults are teratomas and about 85% of them are benign. Case report. We report a case of extragonadal malignant teratoma in a 39-year old man. The computed tomography (CT) scan of the chest revealed the soft-tissue density mass in the middle lobe of the lung. The posterolateral thoracotomy was performed and a mediastinal tumor of 25 cm was completely resected. Histopathological findings confirmed malignant teratoma. One month after the resection the positron emission tomography- computed tomography (PET/CT) scan of the whole body was performed and showed progression of the disease. Patient developed signs of the superior vena cava obstruction and received radiotherapy of the mediastinum and the metastatic lesion of the lumbal vertebra. After radiotherapy, the patient developed paraplegia and urinary incontinence and received the best supportive treatment. Conclusion. Primary extragonadal germ cell tumors have poor prognosis due to their relative chemoresistance and frequent findings of advanced disease after establishing the diagnosis.